Primary carcinoma esophagus with unusual synchronous second malignancies: A case series - Gupta, Surabhi; NA, Aishna (Indian Journal of Case Reports, 2024)
Multiple primary cancer is no longer a rarity. As life expectancy has increased, more individuals are living long enough to develop not only one but also two or more cancers. Herein, we report on three cases of synchronous malignancies associated with the primary esophagus cancer. All three patients posed a challenge for the treatment. These patients carry a dismal prognosis so early diagnosis of subsequent cancer at a curable stage by regular follow-up is encouraged. The early investigation of new symptoms and signs may help to diagnose, initiate early treatment, and reduce the number of deaths from subsequent primary cancers in patients.